2022
DOI: 10.1039/d1fo04146k
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism disorders and lipid mediator changes of mice in response to long-term exposure to high-fat and high sucrose diets and ameliorative effects of mulberry leaves

Abstract: Improvement of n-3 PUFA metabolism disorders plays an important role in anti-obesity modulated by mulberry leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Related studies have found that mulberry leaf water extract can reduce the serum free fatty acid level in hyperglycemic mice (Han et al, 2020). Subsequently, studies have shown that the content of eleven long‐chain fatty acids was significantly reversed in high‐fat diet mice fed with mulberry leaves, this corresponds to our experimental results (Du et al, 2022b). In addition, we noticed that TG had more long‐chain fatty acids in muscle tissue, while TG had more short‐chain fatty acids in fat, which may be related to the presence of some brown fat in muscle, and the activation of UCP1 in brown fat requires long‐chain fatty acids, which corresponds to the presence of more long‐chain fatty acids in muscle (Zhao et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Related studies have found that mulberry leaf water extract can reduce the serum free fatty acid level in hyperglycemic mice (Han et al, 2020). Subsequently, studies have shown that the content of eleven long‐chain fatty acids was significantly reversed in high‐fat diet mice fed with mulberry leaves, this corresponds to our experimental results (Du et al, 2022b). In addition, we noticed that TG had more long‐chain fatty acids in muscle tissue, while TG had more short‐chain fatty acids in fat, which may be related to the presence of some brown fat in muscle, and the activation of UCP1 in brown fat requires long‐chain fatty acids, which corresponds to the presence of more long‐chain fatty acids in muscle (Zhao et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Mulberry leaf is a plant of the genus Mulberry, which is widely distributed in southwest China, Japan, Korea, Europe, and other regions. Mulberry leaf is rich in flavonoids, alkaloids, phenolic acids, and other components, (Srivastava et al, 2003; Zhang et al, 2022) and has hypoglycaemia, lipid‐lowering antioxidant, and other effects (Du et al, 2022a; Liao et al, 2021). Furthermore, mulberry leaves are widely used as functional food and beverage in many Asian countries such as China and Japan (Eva María Sánchez‐Salcedo & Amorós, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaf tea has been recorded for diabetes treatment in “ Compendium of Materia Medica ,” which was booked by the pharmacist Shi‐Zhen Li of the Ming Dynasty in ancient China. Recently, our group has demonstrated that mulberry leaf water or ethanol extracts can improve lipid metabolism disorder, glucose homeostasis, inflammation, oxidative stress, insulin secretion, and gut microbiota imbalance in high‐fat diet and/or streptozotocin (STZ)‐induced obese or type 2 diabetic mice (Du, Li, Lu, Zhang, Zhao, et al, 2022; Du, Li, Lu, Zhang, Zheng, 2002; Du, Li, Lu, Zhang, Zhong, et al, 2022; Ji et al, 2021). However, studies about the impact of mulberry leaf on BCAAs metabolism and relative gut microbiota in T2DM are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaf polyphenols can inhibit body weight and fat accumulation in mice with obesity induced by a HFD, and have potential lipid-lowering and weight-loss effects [14]. Mulberry leaves can also ameliorate lipid metabolism disorders in mice fed a long-term high-fat and high-sugar diet and possess blood-lipid-lowering, antioxidant, and anti-inflammatory properties [15].…”
Section: Introductionmentioning
confidence: 99%